1985
DOI: 10.1037/0021-843x.94.3.346
|View full text |Cite
|
Sign up to set email alerts
|

A PIC profile typology of children and adolescents: I. Empirically derived alternative to traditional diagnosis.

Abstract: This study investigated the utility of a multidimensional instrument, the Personality Inventory for Children (PIC), to serve as the data base for an empirically derived typology of child and adolescent psychopathology. A cluster-analytic technique was applied to T-score ranges of the 12 PIC full-length substantive profile scales for two independent samples of emotionally and behaviorally disturbed children and adolescents that included six criterion marker samples (hyperactive, psychotic, retarded, cerebral dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
29
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 38 publications
1
29
0
Order By: Relevance
“…First, to determine whether the subtypes of psychopathology proposed by Gdowski et al (1985) could be replicated in a heterogeneous neuropsychological sample, thereby supporting the validity of this empirically derived typology. However, based on the results of previous research investigations using specific neuropsychological samples, it was recognized that not all of the subtypes identified by Gdowski et al (1985) may be identified in the present sample.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…First, to determine whether the subtypes of psychopathology proposed by Gdowski et al (1985) could be replicated in a heterogeneous neuropsychological sample, thereby supporting the validity of this empirically derived typology. However, based on the results of previous research investigations using specific neuropsychological samples, it was recognized that not all of the subtypes identified by Gdowski et al (1985) may be identified in the present sample.…”
mentioning
confidence: 99%
“…While these children share important behavioral characteristics that are essential to their diagnostic label, they may differ in other characteristics that affect their general level of adjustment (Gdowski, Lachar & Kline, 1985). For example, children who present with Attention Deficit Hyperactivity Disorder (ADHD) may also display symptomatology related to internalized behavior as well as problematic family or peer relationships (cf.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This profile typology is based on the Personality Inventory for Children (PIC; Wirt, Lachar, Klinedinst, & Seat, 1984), a parent-informant measure of child cognitive, emotional, and behavioral status. To briefly summarize this work, we conducted cluster analyses of PIC profiles to identify profile groups that replicated across independent psychiatric samples of children and adolescents (Gdowski, Lachar, & Kline, 1985). Subsequently, we devised rules to classify the PIC profiles of individual children into this typology .…”
mentioning
confidence: 99%
“…Subsequently, we devised rules to classify the PIC profiles of individual children into this typology . We have also conducted several validation studies of this classification system using different types of external criteria (e.g., teacher and clinician symptom ratings; individually administered intelligence and scholastic tests; special education placement; psychiatric diagnoses; Gdowski et al, 1985;Kline, Lachar, & Boersma, 1987; press; Lachar, Kline, & Boersma, 1986).…”
mentioning
confidence: 99%